FEATURES OF WORLD RECOGNIZED PROFESSIONAL CERTIFICATES OF FINANCIERS AND ACCOUNTANTS, THOSE INTEGRATION TO RUSSIAN UNIVERSITIES’ PROGRAMS - S. V. Anureyev (Финансы: теория и практика)
Russian universities aim at developing their own programs along with increasing the international mobility. Cooperation with recognized English-speaking professional associations (ACA, CFA, ACCA) and making use of their learning materials, exams and certifications is an important factor though so far underestimated. Teaching manuals of the above associations are not expected to contain scientific novelty but they are well styled and include components of abstracts, tests, problem solutions and essays written in the thoroughly edited English language. In this they have an obvious advantage over heavy-style university textbooks or the Business English manual simplifications. Advisable for borrowing is the practice of multiple complex exams rather than the single State Final Examination not unfrequently followed by paid re-examinations ousting traditional hardships of motivating a fee-paying student. The strict methodological support and taking some exams under control of associations offer a contrast to a softer practice of national universities and are more in line with the Unified State Examination of the latest years or the IELTS. The third highest level exams by their form and required skills may be useful for the Russian PhD programs and PhD minimum exams. It is important to understand the specifics of the preparation for a professional English exam which requires every-day systemic diligence instead of our traditional session rush as well as a different number of hours depending on a course and acquired students’ knowledge. All the above is analyzed based on the author’ experience of program accreditation, adjustment of academic disciplines to domestic cases and regulations, engagement of our teachers as the methodologists and interpreters.